The "Give and Take" game: Analysis of a resource sharing game - Mariano, Pedro; Correia, Luís (Zielona Góra: Uniwersytet Zielonogórski)
We analyse "Give and Take", a multi-stage resource sharing game to be played between two players. The payoff is dependent on the possession of an indivisible and durable resource, and in each stage players may either do nothing or, depending on their roles, give the resource or take it. Despite these simple rules, we show that this game has interesting complex dynamics. Unique to "Give and Take" is the existence of multiple Pareto optimal profiles that can also be Nash equilibria, and a built-in punishment action.
Keywords: two player game; cooperation agreements; social behaviours; resource model